THE INFLUENCE OF THE RUSSIAN LANGUAGE AND LITERATURE ON THE DEVELOPMENT OF A COMPETITIVE PERSONALITY (Web of Teachers: Inderscience Research, 2025)
Modern education is aimed not only at the transfer of knowledge, but also at the formation of students' personal and meta-subject competencies that ensure successful self-realization in a rapidly changing world. This article discusses the role of Russian language and literature lessons as the most important components of the humanitarian cycle in the formation of a competitive personality. Particular attention is paid to how language and literary training contributes to the development of creativity, reflection and the ability to interact effectively in different socio-cultural contexts.